Clinical-pathagenetic, Age, Gender, Genetic Aspects of Non-alcoholic Fatty Liver Disease and Nonviral Chronic Hepatitis Without, and also with Comorbid Hypothyroidism; Improving of Their Treatment - Prysyazhnyuk V.; Voloshyn O. (Львівський клінічний вісник)
Introduction. Non-alcoholic fatty liver disease (NAFLD) is the most common ailment among all liver lesions due to an increase in the number of people with obesity, dyslipidemia, increased incidence of type 2 diabetes and metabolic syndrome. The conditions that may be associated with NAFLD are also actively discussed, among which hypothyroidism plays an important role. In recent decades, chronic hepatitis (CH) has become widespread in Ukraine and in the world. The aim of the study. To improve the diagnostic and treatment efficiency of patients with NAFLD and nonviral CH, taking into account clinical and pathogenic, age, gender, genetic factors and the presence of hypothyroidism. Materials and methods. The observation of 311 patients with chronic diffuse liver diseases, including those 188 patients diagnosed with NAFLD (44 among them were diagnosed with hypothyroidism) and 123 nonviral CH patients formed the basis of the clinical research. The control group included 45 practically healthy individuals, representative by age and gender to the examined patients. A complex of modern clinical, biochemical, immune-enzyme, genetic, instrumental and statistical methods of the research were used to solve the tasks in the thesis. Results. Clinical-pathogenic, age, gender peculiarities of clinical course of NAFLD and CH, biochemical blood parameters, lipid, adipokine and cytokine profiles were determined. The correlation between the cytokines plasma content and the biochemical markers of cytolytic, cholestatic, intoxication syndromes, lipid profile are indicative of their important role in pathogenesis of NAFLD and CH. Changes in the structural and functional parameters of the heart, increase of the left ventricle myocardium mass and its index, and ejection fraction reduction were determined with age among NAFLD patients and CH patients. G-allele of glutathione-S-transferase (GST) P1 (A313G) gene occurred more freguently in NAFLD patients as compared to practically healthy individuals and was found to be associated with higher alanine aminotransferase activity and increased atrial natriuretic propeptide, leptin and lower adiponectin concentrations in the blood as compared to the corresponding indicators in patients with AA-genotype. Higher activity of cytolytic syndrome markers, as well as elevated leptin and atrial natriuretic propeptide contents in the blood were investigated in NAFLD patients with Ala-allele of the peroxisome proliferator-activated receptor-y (PPAR-y) gene in comparison with Pro/ Pro genotype carriers. G-allele of GSTP1 gene was found to be associated with a higher alanine aminotransferase activity in the blood in CH patients as compared to AA-genotype carriers. Higher interleukin 10 level in the blood was observed in patients with Ala-allele of PPAR-y gene as compared to Pro/Pro-genotype carriers. NAFLD patients with subclinical and manifested hypothyroidism are characterized by torpid NAFLD clinical course, higher activity of markers of cholestasis, proatherogenic changes of the lipid profile, and adipokine imbalance. NAFLD patients are shown to develop insulin resistance syndrome. In particular, in NAFLD and concomitant subclinical and manifested hypothyroidism patients a significant decrease in J. F. Caro index was determined, and in patients with manifested hypothyroidism the growth of HOMA IR index comparable to respective indicators in NAFLD patients with normal thyroid function was found. On the basis of the obtained data, the treatment process was improved by L-carnitine added to basic therapy in NAFLD and CH patients, resulting in more effective decrease in the activity of cytolytic and cholestatic syndromes markers, decrease of tumor necrosis factor-a content, as manifestations of reducing inflammation processes intensity. In NAFLD patients the above mentioned also contributed to decrease in leptin content together with increased adiponectin concentration in the blood, indicating the normalization of adipokine profile. Additional quercetin prescription to the baseline therapy in observed patients resulted in more effective correction of the indicators of cytolysis, cholestasis and optimization of lipid profile, decrease in tumor necrosis factor-a and atrial natriuretic propeptide contents in the blood. L-carnitine and quercetin administration in addition to the baseline therapy contributes to the reduction in the risk of recrudescent application for medical treatment for NAFLD patients for the following 12 and for CH patients – for the next 6 months, to longer period of compensation of liver disease, reduction of clinical manifestations of diseases in case of required repeated treatment. Conclusions. As a result of the conducted studies, it became possible to improve the diagnostic and treatment effciency of patients with non-alcoholic fatty liver disease and nonviral chronic hepatitis, taking into account clinical and pathogenic, age, gender, genetic factors and the presence of hypothyroidism.